A starting point for addressing product innovativeness in the Fuzzy Front–End. (25th January 2012) - Oliveira, Maicon G.; Phaal, Robert; Probert, David; Cunha, Vitor P.; Rozenfeld, Henrique
Product innovativeness is a primary contingent factor to be addressed for the development of flexible management for the front–end. However, due to complexity of this early phase of the innovation process, the definition of which attributes to customise is critical to support a contingent approach. Therefore, this study investigates front–end attributes that need to be customised to permit effective management for different degrees of innovation. To accomplish this aim, a literature review and five case studies were performed. The findings highlighted the front–end strategic and operational levels as factors influencing the front–end attributes related to product innovativeness. In conclusion, this study suggests that two front–end attributes should be customised: development activities and decision–making approach.